Recent advances in the enzymatic synthesis of sugar-nucleotides using nucleotidylyltransferases and glycosyltransferases. (November 2018) - Ahmadipour, Sanaz; Beswick, Laura; Miller, Gavin J.
Graphical abstract: Sugar-nucleotides are imperative to carbohydrate metabolism and glycoconjugate biosynthesis. Enzymatic methods to access these key materials offer a powerful alternative to traditional chemical synthesis routes. Herein we review recent advances in the enzymatic pyrophosphorylation of glycosyl 1-phosphates for the provision of both native and modified sugar-nucleotides.